Framing the environment under the pandemic: The anthropocentric perspective (a case study of British online media) - Zeniakin, O. S. (My University, 2022)
At the current stage of civilisation development, there arise many issues that attract both public and media attention. One of them is definitely the climate crisis. In 2020, when the world faced the Covid-19 pandemic, there appeared a new incentive to look at our natural world when factories stopped, air flights were cancelled, and human activity was almost at the bottom level concentrating primarily on the big problem — fighting a disease. The pandemic brought to ecolinguists an unprecedented opportunity to investigate how people perceive the natural world in the broad context of a real emergency. This article presents an attempt to look at British online media outlets, both broadsheets and tabloids, and the way the environmental issues are framed on their pages under the circumstances of the world-scale pandemic. The main goal of the research is to find what frames are rendered in the contemporary media discourse in terms of anthropocentrism. The methodology applied to the samples under scrutiny comprised both general scientific methods like those of analysis and synthesis, as well as those of special interest for linguists — critical discourse analysis, multimedia discourse analysis, and frame analysis. The findings of the article present that no matter how difficult the situation is, people remain conservative in their world perception. However, there is slight optimism as some of the anthropocentric frames clear the way for a new paradigm of human-and-nature relations — ecocentrism.
Keywords: anthropocentrism; critical discourse analysis; ecolinguistics; frame theory; media discourse